Basic archival principles and book preservation in Nigerian libraries (2015)
In view of the vital importance of archives administration and preservation to access information resources, the paper takes a look at the archival principles of arrangement and description as well as book preservation in Nigerian libraries. It analyses the various levels of arrangement through which the physical control of archival materials is established. The value of archival description as a means of facilitating the intellectual control of and access to archival materials is also identified. It highlights the variation in access procedure in archives and libraries and concludes that the variation notwithstanding, access to information resources goes to the very root of archives and libraries in Nigeria. The strategic importance of preservation in facilitating access to information resources is also explored. Factors that account for book deterioration, particularly in the tropics are identified. Finally, suggestions are made for tackling the challenges of deterioration of information resources in Nigeria.